Pemberdayaan Ekonomi Masyarakat Desa Kampili melalui Inovasi Minuman Cincau Kekinian - Ansar, Ansar; Arfah, Aziza Noor Sheha; Mahi, Faizah; Hasan, Hasna (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Empowerment of Kampili Village Community Economy Through Innovative Cincau Drinks The utilization of cincau as a fiber-rich food ingredient in Kampili Village is still limited, even though the current beverage trend opens significant economic opportunities. This community service aims to empower the economy of the Kampili Village community through the program "Management of Innovative Cincau-Based Beverages." The implementation method included socializing the economic potential of cincau and providing technical training on processing cincau into innovative drink products, such as Cincau Cappuccino, which was conducted at the Kampili Village Hall on April 30, 2025. The activity was attended by 25 participants consisting of PKK mothers and Karang Taruna youth. The evaluation results showed that 85% of participants successfully mastered the practical skills of cincau processing, and there was a significant increase in understanding of entrepreneurial aspects, including hygiene, market potential, cost calculation, and packaging strategies. This program succeeded in fostering entrepreneurial enthusiasm and laid the foundation for the development of innovative cincau drink businesses as an alternative income source, thereby contributing to the economic improvement of the Kampili Village community.